WAYS TO IMPROVE RESIDUAL THYROID TISSUE AFTER SURGERY FOR DIFFUSE TOXIC GOITTER IN THE ELDERLY AND SENILE PEOPLE - Narzullaev Sh.Sh. (Research Focus International Scientific Journal, 2023)
one of the pressing problems of modern medicine and endocrine surgery is the problem of the approach to surgical treatment of patients with toxic goiter. The relevance of this problem is associated with many issues affecting both the choice of surgical intervention and ways to reduce postoperative complications and relapse of the disease. Surgical treatment of nontoxic goiter and thyroid nodules leads to a significant improvement in the quality of life of patients. The article examines the results of treatment of 128 patients for non-toxic goiter and thyroid nodules. An analysis of the effectiveness of operations was carried out.